Progressive Pulmonary Fibrosis: Where Are We Now? - Hyung Koo Kang; Jin Woo Song (Tuberculosis and Respiratory Diseases, 2024)
Interstitial lung diseases (ILDs) are a diverse collection of lung disorders sharing similar features, such as inflammation and fibrosis. The diagnosis and management of ILD require a multidisciplinary approach using clinical, radiological, and pathological evaluation. Progressive pulmonary fibrosis (PPF) is a distinct form of progressive and fibrotic disease, occurring in ILD cases other than in idiopathic pulmonary fibrosis (IPF). It is defined based on clinical symptoms, lung function, and chest imaging, regardless of the underlying condition. The progression to PPF must be monitored through a combination of pulmonary function tests (forced vital capacity [FVC] and diffusing capacity of the lung for carbon monoxide), an assessment of symptoms, and computed tomography scans, with regular follow-up. Although the precise mechanisms of PPF remain unclear, there is evidence of shared pathogenetic mechanisms with IPF, contributing to similar disease behavior and worse prognosis compared to non-PPF ILD. Pharmacological treatment of PPF includes immunomodulatory agents to reduce inflammation and the use of antifibrotics to target progressive fibrosis. Nintedanib, a known antifibrotic agent, was found to be effective in slowing IPF progression and reducing the annual rate of decline in FVC among patients with PPF compared to placebos. Nonpharmacological treatment, including pulmonary rehabilitation, supplemental oxygen therapy, and vaccination, also play important roles in the management of PPF, leading to comprehensive care for patients with ILD. Although there is currently no cure for PPF, there are treatments that can help slow the progression of the disease and improve quality of life.